Developing teachers' research capacity: the essential role of teacher education. Issue 1 (2nd January 2021) - Tatto, Maria Teresa
ABSTRACT: With a focus on the US, I briefly review the literature to examine current trends, and outline a typology of what is meant by educational research for teaching by, with and for teachers, followed by a discussion of why it is important for educators to engage in and commit to such research. The key question in this article is what kinds of research are helpful for program improvement and for high-quality teaching and learning? A follow-up question is where should teachers learn to do such research and what would it mean to be a proficient teacher-researcher? These questions lead to an exploration of the role of teacher educators in helping teachers learn diverse epistemologies, theoretical perspectives, and methodologies to engage in researching the complexity involved in enriching and improving teacher education, teaching and learning.